Cost-Effectiveness Analysis of Fracture Liaison Services Compared with Standard of Care in the Secondary Prevention of Fragility Fractures in Spain - Naranjo A; Prieto-Alhambra D; Sánchez-Martín J; Pérez-Mitru A; Brosa M (Dove Medical Press, 2022)
Antonio Naranjo,1 Daniel Prieto-Alhambra,2 Julián Sánchez-Martín,3 Alejandro Pérez-Mitru,3 Max Brosa3 1Department of Rheumatology, Hospital Universitario de Gran Canaria Dr. Negrín, Universidad de Las Palmas de Gran Canaria, Las Palmas de Gran Canaria, 35011, Spain; 2NIHR Musculoskeletal Biomedical Research Unit, University of Oxford, Oxford, UK; 3Market Access Area, Pharmalex Spain, Barcelona, SpainCorrespondence: Alejandro Pérez-Mitru, Market Access Area, Pharmalex Spain, C/ Comte d'Urgell, 240, 2-D, Barcelona, 08036, Spain, Tel +34 932 521 377, Fax +34 937 379 984, Email alejandro.perez@pharmalex.comPurpose: To assess the cost-effectiveness of a Fracture Liaison Service (FLS) compared with standard care for the secondary prevention of fragility fractures in Spain.Methods: Patients with osteoporosis and an initial fragility fracture who were candidates to initiate osteoporosis treatment (mean age 65 years, 90.7% female) were included in the model. Disease progression was simulated with a Markov model through seven health states (with and without osteoporosis treatment, subsequent hip, vertebral, forearm and humerus fracture, and death). A time horizon of 10 years and a 6-month duration per cycle was set. Clinical, economic, and quality of life parameters were estimated from the literature and Spanish clinical practice. Resource use and treatment patterns were validated by an expert panel. The Spanish National Health System (SNS) perspective was adopted, taking direct costs (€; 2020) into account. Effectiveness was measured in life-years gained (LYG) and quality-adjusted life years gained (QALYs). A discount rate of 3% was applied to costs and outcomes. The uncertainty of the parameters was assessed using deterministic, scenario and probabilistic sensitivity analyses (1000 iterations).Results: Setting up a FLS for the secondary prevention of fragility fractures in Spain would provide better osteoporosis treatment initiation and persistence. This would reduce subsequent fragility fractures, disutilities and deaths. FLS would have greater clinical benefits (0.008 and 0.082 LYG and QALY gained per patient, respectively) and higher costs (€ 563.69 per patient) compared with standard care, leading to an incremental cost-utility ratio of € 6855.23 per QALY gained over the 10 years horizon. The sensitivity analyses showed limited dispersion of the base case results, corroborating their robustness.Conclusion: From the SNS perspective and considering Spanish willingness-to-pay thresholds, the introduction of FLS for the secondary prevention of fragility fractures would be a cost-effective strategy.Keywords: economic evaluation, osteoporotic fracture prevention, fracture liaison service, Spain